Epistemological Integration of Hisab and Rukyat in Thantawi Jauhari’s Scientific Exegesis - Azizah, Nayla Alfi; Fata, Zahrul (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2026)
The differences in determining the beginning of the Hijri month in Indonesia reflect epistemological distinctions between the methods of hisab (astronomical calculation) and rukyat (crescent observation), which are often positioned dichotomously. However, previous studies have generally addressed their integration at the level of practical fiqh and have not specifically constructed the epistemological relationship between the concepts of ḥusbān and ahillah in the Qur’an. This study aims to analyze the epistemological construction of hisab and rukyat within the framework of scientific exegesis (tafsir ‘ilmi) by Tantawi Jauhari on QS. Yunus:5 and QS. Al-Baqarah:189. This study employs a qualitative library approach using tafsir ‘ilmi, with data analyzed descriptively and analytically based on classical and contemporary tafsir as well as relevant scientific literature. The findings reveal that, in Tantawi Jauhari’s perspective, ḥusbān represents the order and precision of cosmic calculation, while ahillah reflects the empirical dimension of crescent visibility as a marker of religious time. These two concepts are not oppositional but form an integrated epistemological system. This study contributes theoretically to strengthening the integration of revelation and science in Qur’anic exegesis and offers practical implications for developing a more coherent and dialogical model of determining the Hijri calendar through the integration of hisab and rukyat.